Myoepithelioma-like hyalinizing epithelioid tumors of the palm: A case report - Xiaoxiao Bao; Qianqian Lu; Bifei Huang; Xiaowei Zhang (Journal of International Medical Research)
Myoepithelioma-like hyalinizing epithelioid tumors (MHETs) are distinct soft tissue neoplasms characterized by their unique histological presentation, including myoepithelioma-like hyalinization and an epithelioid-cell pattern. A defining molecular characteristic of these tumors is the presence of a novel OGT :: FOXO gene fusion. Their distinct morphology makes diagnosis challenging because they can be mistaken for other soft tissue tumors. We report the case of a 71-year-old man who was admitted to our hospital with a 1-year history of a palpable mass on the left palm. Physical examination revealed a well-defined, mobile mass on the lateral aspect of the left palm, measuring 2.0 × 3.0 cm, with moderate consistency. The tumor was surgically excised, and postoperative pathology based on immunohistochemical staining and tissue morphology confirmed the diagnosis of MHET. The tumor cells exhibited diffuse positivity for CD34 and focal positivity for EMA. At the 3-month follow-up post-surgery, there was no evidence of recurrence or distant metastasis. MHETs are typically observed as superficial, well-circumscribed masses without the histological features of malignancy. Given the distinct tissue morphology and the recent identification of this tumor type, clinicians and pathologists must be aware of these features to facilitate accurate diagnosis and inform treatment strategies.